Targeting CEA in metastatic triple negative breast cancer with image-guided radiation followed by Fab-mediated chimeric antigen receptor (CAR) T-cell therapy - Aniogo, Eric; Kujawski, Maciej; Awuah, Dennis; Cha, Seung E.; Espinosa, Ruby; Hui, Susanta; Ghimire, Hemendra; Yazaki, Paul J.; Brown, Christine E.; Wang, Xiuli; Shively, John E. (Frontiers in Immunology, 2024)
IntroductionAlthough CAR-T cell therapy has limited efficacy against solid tumors, it has been hypothesized that prior treatment with Image-Guided Radiation Therapy (IGRT) would increase CAR-T cell tumor infiltration, leading to improved antigen specific expansion of CAR-T cells.MethodsTo test this hypothesis in a metastatic triple negative breast cancer (TNBC) model, we engineered two anti-CEA single-chain Fab (scFab) CAR-T cells with signaling domains from CD28zeta and 4-1BBzeta, and tested them in vitro and in vivo.ResultsThe anti-CEA scFab CAR-T cells generated from three different human donors demonstrated robust in vitro expression, expansion, and lysis of only CEA-positive TNBC cells, with the CD28z-CAR-T cells showing the highest cytotoxicity. IFN-γ and granzyme B release assays revealed significantly higher IFN-γ production at a 4:1 effector-to-target (E:T) ratio in CD28z-CAR-T cells compared to 4-1BBz-CAR-T cells. Treatment of CEA-positive TNBC MDA-MB231 xenografts in the mammary fat pads of NSG mice, that produced spontaneous lung metastases over time, resulted in significant tumor growth reduction compared to either therapy alone (p<0.01). Immunohistochemical (IHC) analysis revealed that only combined IGRT and CAR-T therapy resulted in the elimination of lung metastases.DiscussionThese findings demonstrate that the combination of IGRT and anti-CEA scFab CAR-T therapy induces a strong antitumor response, effectively targeting both the primary tumor and distant metastatic lesions in the lungs, thus demonstrating that IGRT enhances CAR-T cell infiltration, persistence, and overall efficacy within both primary and metastatic lesions.